All‐Metal‐Organic Framework‐Derived Battery Materials on Carbon Nanotube Fibers for Wearable Energy‐Storage Device. Issue 12 (11th October 2018) - Zhang, Qichong; Zhou, Zhenyu; Pan, Zhenghui; Sun, Juan; He, Bing; Li, Qiulong; Zhang, Ting; Zhao, Jingxin; Tang, Lei; Zhang, Zengxing; Wei, Lei; Yao, Yagang
Abstract: The ever‐increasing demands for portable and wearable electronics continue to drive the development of high‐performance fiber‐shaped energy‐storage devices. Metal‐organic frameworks (MOFs) with well‐tunable structures and large surface areas hold great potential as precursors and templates to form porous battery materials. However, to date, there are no available reports about fabrication of wearable energy‐storage devices on the utilization of all‐MOF‐derived battery materials directly grown on current collectors. Here, MOF‐derived NiZnCoP nanosheet arrays and spindle‐like α‐Fe2 O3 on carbon nanotube fibers are successfully fabricated with impressive electrochemical performance. Furthermore, the resulting all‐solid‐state fiber‐shape aqueous rechargeable batteries take advantage of large specific surface area and abundant reaction sites of well‐designed MOF‐derived electrode materials to yield a remarkable capacity of 0.092 mAh cm −2 and admirable energy density of 30.61 mWh cm −3, as well as superior mechanical flexibility. Thus, this research may open up exciting opportunities for the development of new‐generation wearable aqueous rechargeable batteries. Abstract : A prototype wearable aqueous rechargeable battery using all‐metal‐organic framework‐derived battery materials on carbon nanotube fibers as binder‐free electrodes is demonstrated. The resulting devices exhibit excellent electrochemical performance. Such a novel concept of fiber‐shaped aqueous rechargeable batteries opens new opportunities for flexible energy‐storage technologies.